VD_FINDINFO Jug / 2014 / 61 vom 3. Oktober 2013 - VD Tribunal cantonal (2013)
RETRAITVOIE DE DROIT, FRAIS JUDICIAIRES, RECOURS JOINT, APPELCPP | 386 al. 2 let. a CPP (CH), 401 al. 3 CPP (CH), 428 al. 1 CPP (CH)